Reasons for Adding Different Tastes: An Example of Sprinkling Salt on Watermelon and Its Relation to Subjective Taste Perception, Taste Preference, and Autistic Traits. (13th February 2023) - Chen, Na; Watanabe, Katsumi; Kobayakawa, Tatsu; Wada, Makoto
Abstract : Each basic taste can be perceived differently due to stored knowledge and differences in receptor properties. Depending on how these tastes are perceived, eating behavior may change. In this study, we examined the relationships between subjective feelings of taste perception, taste preferences, and autistic traits with the behavior of adding flavor to food using an example of sprinkling salt on watermelon. From an online questionnaire survey among a general Japanese population, we found that salty and sour tastes could be subjectively perceived more quickly than sweet and umami tastes, in line with our expectations. Moreover, the hedonic responses to watermelon with salt were negatively correlated with a preference for bitter taste, i.e., those participants who dislike bitter taste sensations tended to enjoy watermelon with salt more. There was no correlation between the hedonic response to watermelon with salt and the subjective feeling of taste perceptions and autistic traits and no correlation between autistic traits, and the subjective feeling of taste perceptions and taste preferences. These results suggest that adding different tastes could be influenced by taste preferences; thus, the addition of a different taste was thought to be related to an unconscious motivation to reduce bitterness.